2019
DOI: 10.1101/570739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive head-to-tail insertions of DNA templates mask desired CRISPR/Cas9-mediated genome editing events

Abstract: CRISPR/Cas9 mediated homology-directed DNA repair is the method of choice for precise gene editing in a wide range of model organisms, including mouse and human.Broad use by the biomedical community refined the method, making it more efficient and sequence specific. Nevertheless, the rapidly evolving technique still contains pitfalls. During the generation of six different conditional knock-out mouse models, we discovered that frequently (sometimes solely) homology-directed repair and/or non-homologous end-joi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…elegans 38 and fish 39 using the CRISPR-Cas9 system. Most recently, unintended on-site template DNA insertion was reported as key findings in work with CRISPR edited mice 40 and cattle 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…elegans 38 and fish 39 using the CRISPR-Cas9 system. Most recently, unintended on-site template DNA insertion was reported as key findings in work with CRISPR edited mice 40 and cattle 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PCR conditions that are designed to amplify a short region including the target site may fail to amplify an unintended insertion, leading to an incorrect characterization of the editing event. There are indeed reports that PCR failed to detect multiple integration events 25,40,41 , thus PCR reagents and extension times should be selected to amplify much larger than expected fragments. For edited lines that are intended for commercialization, it will be necessary to perform long read sequencing or whole genome sequencing to determine exact nature of edited events.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Dickinson et al 12 , using CRISPR/Cas9 with a template plasmid in C. elegans , reported the integration of a second copy of the template at the target site. Additional publications using CRISPR/Cas9 with double stranded DNA (dsDNA) repair templates showed that the dsDNA templates can form multimers that integrate into the target site in fish 13 and mice 14 .…”
Section: Articlementioning
confidence: 99%
“…Using the Cas9 protein/sgRNA ribonucleoproteins (RNPs) to perform genome editing offers several advantages than with the co-transformation of the Cas9 expression plasmid and sgRNA. One of the major advantages is that the transformation of Cas9 RNPs alleviates the possibility of the integration of a genetic material to a non-targeted region of the genome [23][24]. In addition, Cas9 and sgRNA can form a stable ribonucleoprotein in vitro, which reduces the likelihood of RNA degradation when compared to that with the Cas9 mRNA/sgRNA transformation.…”
Section: Discussionmentioning
confidence: 99%